تحليل دور مبادئ حوكمة المنظمات في تبني مؤشرات الأداء الريادي دراسة تحليلية لآراء أعضاء مجالس الجامعات الخاصة في إقليم كوردستان- العراق - محمد, جلال عبدالله; ميرخان, خالد حمد امين (Sulaimani Journal for Humanities, 2018)
This study aims to analyze the role of the corporate governance principles in the adoption of the entrepreneurial performance indicators through identify the relationship and impact between the principles of organizational governance and the indicators of entrepreneurial performance in the private universities sector in the Kurdistan Region - Iraq and to recognize the validity of the study hypotheses with achieve its objectives. In order to achieve this objective, the researchers have used the analytical method by using the questionnaire which were distributed to the heads and members of the councils of private universities in the region, the sample included (110) members of the heads and members of the Councils of private universities in the Kurdistan Region of Iraq, who are considered as the top leaders in those universities which includes (12) Universities. In conclusion of their analysis, the researchers reached that the principles of corporate governance contribute significantly to achieving the indicators of entrepreneurial performance and the governance of organizations is recognized as an important administrative entrance which helps the organizations achieving the entrepreneurial performance. In the light of the results that have been reached, the researchers presented a set of recommendations such as establish the strategic thinking of the principles of corporate governance and make it an integral part of the strategy of private universities and other organizations in order to gain the high levels of entrepreneurial performance.